Biomass energy consumption and economic growth: ARDL analysis - Bildirici, Melike E. (TAYLOR & FRANCIS INC, 2016)
This article investigated the causality relation between biomass energy consumption and economic growth in Australia, Canada, Denmark, Finland, France, Japan, the UK and the US by using the autoregressive distributed lag (ARDL) bounds testing method, and Granger causality test. The dataset covers the 1980-2010 period. For Canada, France, the UK and the US, the results of short-run causality determined the evidence that the conservation hypothesis is supported and the evidence of the growth hypothesis for Australia, Belgium, Finland and Japan. Strong causality results found the evidence of feedback hypothesis for the US, UK, and France.
Keywords: ARDL; biomass energy consumption; economic growth; Granger Causality test; VEC; BOUNDS TESTING APPROACH; ELECTRICITY CONSUMPTION; COUNTRIES; INDIA; GNP; CAUSALITY; AUSTRALIA; GDP; Energy & Fuels